Legal Position of Business Competition Law in the Perspective of Legal Certainty in Indonesia: A Normative Study of Law No. 5 of 1999 Post-Omnibus Law - Mohammad Reza; M. Hawin; Ningrum Natasya Sirait (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the legal position of business competition law within Indonesia’s legal system following amendments introduced by the Omnibus Law, as well as its implications for legal certainty in competition case resolution. This research employs a normative legal method through legislative, conceptual, and case approaches. The findings indicate that Law No. 5 of 1999, after being amended by the Omnibus Law, places competition law within the administrative non-criminal legal framework, yet still leaves several legal uncertainties, particularly regarding the authority of the Business Competition Supervisory Commission (KPPU) in conducting investigations. These uncertainties result in inconsistencies in law enforcement and overlaps with other legal systems. This study recommends a comprehensive procedural framework for business competition law, reinforcing KPPU’s position as an auxiliary state institution with full authority over administrative investigations, along with improvements in evidence mechanisms.